The effect of constant practice in transfer tests - Guilherme Menezes Lage; Tércio Apolinário-Souza; Maicon Rodrigues Albuquerque; Leonardo Luiz Portes; Marcelo da Silva Januário; Marcio Mário Vieira; Herbert Ugrinowitsch
Abstract BACKGROUND There is aconsensus that repetition observed in constant practice producesminimalbenefits to the transfer of learning. OBJECTIVE The purpose of this study was to investigatein 3 experiments the effects of constant practicein transfer contexts. METHODOLOGY Participants were asked during acquisition phase, in all experiments, to press four keys sequentially with different requirements of absolute timing in a same relative timing structure. In the transfer tests, they were tested in a novel absolute timing criterion. RESULTS The results of experiment 1 and 2 showed that the relative timing structure was maintained only when the transfer required parameter scaling close to the parameter value practiced in acquisition. The transfer parameter that is far to the parameter practiced did not affect the movement parameterization. The result of experiment 3 showed that relative timing structure is disrupted in the transfer test when constant practice has high and low amount of practice. CONCLUSION Some specific aspects interfere in the transfer test when constant practice is experienced.